A preliminary reading of Maragtas as political myth - Talledo, Tomasito T. (2007)
This paper reads the Maragtas narrative earlier textualized by Pedro Alcantara Monteclaro (1907) as a foundation of political myth. As political myth, it seeped into the works of esteemed Ilonggo writers Magdalena Gonzaga Jalandoni (Hiligaynon, 1958) and Ricaredo D. Demetillo (English, 1961 & 1975). These creative appropriations, among others, have disposed the Maragtas to loom as a mythic frame of a hierarchical social order. As foundational myth, the Maragtas supplied a convincing national political story that, in the final analysis, responded to and justified the desideratum of the Philippine state.